2007
DOI: 10.1007/s11595-005-2315-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electric properties of (1−x)(Bi1/2Na1/2) TiO3-xBaTiO3 Systems

Abstract: The structural, dielectric and piezoelectric properties of (1-x)(Bi 1/2 Na 1/2 ) TiO 3 -xBaTiO 3 ceramics were investigated for the compositional range, x=0.02, 0.04, 0.06, 0.08, 0.10. The samples were synthesized by a conventional solid-state reaction technique. All compositions show a single perovskite structure, and X-ray powder diffraction patterns can be indexed using a rhombohedral structure. Lattice constants and lattice distortion increase while the amount of BaTiO 3 increases. The X-ray diffraction re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The structure and lattice parameters of BNBT materials have been determined by using a standard computer program "POWD" (interpretation and indexing program by E. Wu, school of physical sciences, Flinders University of South Australia, Bed Ford Park, Australia). It is obvious from the Figure 1 all the peaks in the XRD pattern of the BNBT are correspond to the BNT (3.886Å) phase with rhombohedral structure as reported by different researchers [19][20][21]. All the XRD peaks obtained in compositions are indexed and found to be single phase with rhombohedral structure.…”
Section: Xrd Analysissupporting
confidence: 58%
“…The structure and lattice parameters of BNBT materials have been determined by using a standard computer program "POWD" (interpretation and indexing program by E. Wu, school of physical sciences, Flinders University of South Australia, Bed Ford Park, Australia). It is obvious from the Figure 1 all the peaks in the XRD pattern of the BNBT are correspond to the BNT (3.886Å) phase with rhombohedral structure as reported by different researchers [19][20][21]. All the XRD peaks obtained in compositions are indexed and found to be single phase with rhombohedral structure.…”
Section: Xrd Analysissupporting
confidence: 58%
“…EG can exfoliate to an insulating carbonaceous layer on the surface of composites when exposed to high temperatures 19 . The flame retardant performance of EG in thermosetting resins is very high 19,20 but it is much lower in thermoplastic, so it is very difficult to reach the V‐0 classification of the UL94 vertical burning (UL94‐V) test in the thermoplastic composites containing only EG 21–23 . Consequently, a combination of EG and other flame retardant additives in thermoplastics is necessary to generate synergistic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Between the polymer concrete and GFRP, shear stress and normal stress applied 24. The GFRP‐reinforced polymer concrete used in this study was of the precast type so that the following equations, suggested by Roberts,8 were used for stress analysis: where σ max is the maximum normal stress, τ max is the maximum shear stress, K s = G a ( b a / d a ) is the shear stiffness per unit length, K n = E a ( b a / d a ) is the normal stiffness per unit length, F 0 is the global shear force in the beam, E frp is the Young's modulus of FRP, b frp is the width of FRP, d frp is the depth of FRP, M 0 is the global bending moment, I is the geometrical moment of inertia of the full composite, b a is the width of the adhesive layer, h frp is the effective depth of FRP, h is the depth of neutral axis, I frp is the geometrical moment of inertia, G a is the shear modulus of the adhesive, d a is the depth of the adhesive layer, and E a is the Young's modulus of the adhesive.…”
Section: Resultsmentioning
confidence: 99%